Механізм державного управління інвестуванням в рекреаційній сфері - Бондаренко, Юлія Григорівна (Національний університет "Львівська політехніка", 2019)
Дисертацію присвячено розкриттю теоретико-методологічних основ та розробці практичних рекомендацій щодо формування механізму державного управління інвестуванням в рекреаційній сфері. Проаналізовано та визначено місце і роль рекреації та її вплив на психофізичний і емоційний стан населення зокрема. Удосконалено комплексну модель активізації інвестиційних процесів у формуванні рекреаційно-туристичного продукту-послуги. Удосконалено практичні підходи до формування стратегічних напрямів розвитку рекреаційної сфери з урахуванням доцільності формування рекреаційних кластерів як базису для утворення рекреаційного простору. Розроблено матрицю вибору стратегічних напрямків розвитку України у розрізі її областей. Результатом дослідження є розроблення моделі послідовного підвищення інвестиційної привабливості рекреаційної сфери у системі державного адміністрування з врахуванням попередньо сформованого механізму управління. Диссертация посвящена раскрытию теоретико-методологических основ и разработке практических рекомендаций по формированию механизма государственного управления инвестированием в рекреационной сфере. Проанализированы и определены место и роль рекреации и ее влияние на психофизическое и эмоциональное состояние населения в частности. Усовершенствована комплексная модель активизации инвестиционных процессов в формировании рекреационно-туристического продукта-услуги. Усовершенствовани практические подходы к формированию стратегических направлений развития рекреационной сферы с учетом целесообразности формирования рекреационных кластеров как базиса для образования рекреационного пространства. Разработана матрица выбора стратегических направлений развития Украины в разрезе ее областей. Результатом исследования является разработка модели последовательного повышения инвестиционной привлекательности рекреационной сферы в системе государственного администрирования с учетом предварительно сформированного механизма управления. The dissertation is dedicated to the disclosure of theoretical and methodological foundations and the development of practical recommendations for the formation of the mechanism of state administration of investments the recreational sector. The current state of recreational sphere of Ukraine and its investment suitability are analyzed. The place and role of recreation and recreational sector organizations in the national economy and their influence on the psychophysical and emotional state of the population are determined. It is proved that the factor of trust in the economic system of the state, including all its institutions, is an important component, which prompts organizations to re-invest their assets, taking into account risk factor, the payback period in long-term perspective. In general, the factor of trust and the level of qualification of government bodies contribute significantly to the creation of favorable conditions for the development of the state, including economics, social, environmental components of life. In addition, structural components of the recreational sphere are studied and clarified in the research, which include: consumers of recreational product (recreators); recreational sphere organizations; state, local authorities; non-governmental organizations (public organizations). Their interdependence and interaction are analyzed, their influence the formation of the mechanism of management of investment processes is studied by determining the outcome of the expectation of each subject from the mutual cooperation. It is concluded that the state carries out social policy regarding the population as a consumer of recreational services and a political and economic function concerning recreational organizations. Therefore, the recreational sphere requires state regulation in two directions: the popularization of recreational activities in society and the development of the economic branch of recreational services. It is proposed to consider the population as the main element of the formation of the state and as the creator of its material wealth. In particular, it has been determined that, because of the function of its consumption function, population is a significant source of income for recreational sector organizations and, accordingly, affects the growth of investments directed towards the development of the recreational sphere. Accordingly, in the research population is considered to be the main forming capital of the state, which, in combination with the land (territory) and its natural wealth, forms the state as a sovereign political, economic territorial unit. A comparative analysis of the institutional conditions for the functioning of the recreational sphere in Ukraine and abroad has been carried out. The examples of the organization of recreational leisure in the world and the normative and legal documents regulating their activities are presented, in particular in such states as: Poland, Canada, USA. It is determined that the main function of state institutions is to create conditions for the effective functioning of economic entities of the market system, which include recreational sphere organizations. The role of public administration in conducting recreational activity in Ukraine and preservation of its natural and recreational sphere is substantiated. It is stated that the recreational sphere is represented only in one Order "On Approval of the Regulation" On recreational activities within the territories and objects of the nature reserve fund of Ukraine ". Theoretical and scientific approaches to the definition of the concept of "organization of the recreational sphere" are generalized and systematized and their place in the cyclical development of the economy is determined. Comparison of capital investments by types of economic activity for the period from 2010 to 2017 is conducted. A complex model of activation of investment processes in the formation of a recreational product-service has been improved taking into account the existing recreational potential of the territory and the characteristics of consumer behavior of the population depending on the income level of the family. The types of activities that characterize recreation and tourism as economic categories are investigated, where the general similarity of these concepts is clarified. As a result, activities that are not inherent in tourism activity are highlighted, but it distinguishes recreation and points to considerably wider limits of recreation in comparison with tourism. The research introduces the author's vision of the mechanism of investment processes administration at the level of state authorities is presented, which will promote the effective development of the recreational sphere and will create an appropriate recreational environment. This mechanism has become the basis for developing a mechanism for managing investment processes in recreational sphere organizations. According to the results of the research, the concept of the mechanism of administration of investment processes and determining the nature of its influence on the organization of the recreational sphere, a generalized model of interdependence and complementarity of the participants of the investment process has been proposed, which identifies the needs of all participants whose satisfaction will contribute to the development of these organizations. Practical approaches to the formation of strategic directions of recreational sphere development have been improved, taking into account the expediency of forming recreational clusters as a basis for the creation of a recreational space in the developed territories in all regions of Ukraine. The matrix of the choice of strategic directions of development of Ukraine in the context of its regions with the consideration of recreational potential and their investment level is developed. The result of the research is the development of a model for the consistent increase of the investment attractiveness of the recreational sphere in the system of state administration taking into account the above mentioned administration mechanism. The necessity of in-depth study of the mechanism of investment management in the recreational sphere is proved.
Механизм государственного управления инвестиционными процессами в организациях рекреационной сферы
Mechanism of state administration of investing in recreational sphere
Keywords: механізм; інвестиції; механізм державного управління інвестуванням; рекреація; організації рекреаційної сфери; механизм; инвестиции; механизм государственного управления инвестированием; рекреация; организации рекреационной сферы; mechanism; investment; mechanism of state administration investment; recreation; organization of recreational sphere; 330.322.4:338.24:338.48-53